Chemical utilization of hydrogen from fluctuating energy sources – Catalytic transfer hydrogenation from charged Liquid Organic Hydrogen Carrier systems. (12th January 2016) - Geburtig, Denise; Preuster, Patrick; Bösmann, Andreas; Müller, Karsten; Wasserscheid, Peter
Abstract: Liquid Organic Hydrogen Carrier (LOHC) systems offer a very attractive way for storing and distributing hydrogen from electrolysis using excess energies from solar or wind power plants. In this contribution, an alternative, high-value utilization of such hydrogen is proposed namely its use in steady-state chemical hydrogenation processes. We here demonstrate that the hydrogen-rich form of the LOHC system dibenzyltoluene/perhydro-dibenzyltoluene can be directly applied as sole source of hydrogen in the hydrogenation of toluene, a model reaction for large-scale technical hydrogenations. Equilibrium experiments using perhydro-dibenzyltoluene and toluene in a ratio of 1:3 (thus in a stoichiometric ratio with respect to H2 ) yield conversions above 60%, corresponding to an equilibrium constant significantly higher than 1 under the applied conditions (270 °C). Highlights: Transfer hydrogenation using LOHC systems offers a highly attractive way to use hydrogen from intermittent electrolysis in steady-state chemical production processes. The LOHC compound perhydro-dibenzyltoluene can be applied as sole source of hydrogen in catalytic transfer hydrogenation reactions. Commercial Pt-based catalysts perform best in this reaction.